Pengaruh Kualitas Makanan, Kualitas Pelayanan dan Lokasi Terhadap Kepuasan Pelanggan Pada Rumah Mama Alya Di Bandar Lampung - Yunita, Rintis Nona; Fuadi, Selamet (Universitas Muhammadiyah Metro, 2021)
THE EFFECT OF FOOD QUALITY, QUALITY OF SERVICE, AND LOCATIONON CUSTOMER SATISFACTION AT HOME EAT MAMA ALYA IN BANDAR LAMPUNG Of Rintis Nona Yunita Npm. 17610054 ABSTRACT Rintis Nona Yunita Npm. 17610054 The Influence of Food Quality, Service Quality, and Location on Customer Satisfaction at Mama Alya Restaurant in Bandar Lampung Advisors (1) Ratmono, S.E, M.M (2) H. Suwarto, S.E M.M A new concept in the restaurant business that combines the development of food quality, service quality, and location to customer satisfaction. The dining experience includes an assessment of the overall customer experience from the quality of food and service to the location of the restaurant. Therefore, by understanding what satisfies customers and directs them to repurchase, say positive things and recommend restaurants to others. This study aims to determine 1) To determine whether food quality affects customer satisfaction at Mama Alya's restaurant in Bandar Lampung. 2) To find out whether Service Quality affects customer satisfaction at Mama Alya Restaurant in Bandar Lampung 3) To find out whether Location affects customer satisfaction at Mama Alya Restaurant in Bandar Lampung. 4) To find out whether Food Quality, Service Quality, and Location affects customer satisfaction at Mama Alya's restaurant in Bandar Lampung. This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data on respondents who have certain information, allowing researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population is the consumer of the restaurant Mama Alya. The sampling technique used accidental sampling with a sample size of 75 people. The data collection technique used a questionnaire with a Likert scale. The results showed that: 1) there is a positive effect of food quality on customer satisfaction. 2) there is a positive effect of service quality on customer satisfaction 3) there is a positive influence of location on customer satisfaction. 4) there is a positive influence on food quality, service quality and location together on customer satisfaction. Keywords: Food Quality, Service Quality And Customer Satisfaction Location